How Collostructional Analysis Contributes to the Description of Argument Structure Constructions with Slots for that-and Infinitive Clauses - Uhrig, Peter; Herbst, Thomas (Zeitschrift für Anglistik und Amerikanistik, 2024)
This article analyses two English constructions, the monotransitive that-cl construction and the np+to-infinitive construction. In particular, we will show how the principles of collostructional analysis can be used to establish collo-profiles for argument structure constructions, i.e.The verbs to be found very frequently in a construction, and how such collo-profiles can provide important cues for a semantic characterization of these constructions. In this case, we find that the that-clause cxn contains a large number of verbs of reporting, indicating a factual character of the construction in contrast to the infinitive construction that expresses a kind of modal meaning.
CRIS-Team Scopus Importer:2024-12-06
Keywords: CASA ConstruCtiCon; collo-profile; collostructional analysis; construction grammar; infinitive constructions; that-clause constructions